Brisingr, or, The seven promises of Eragon Shadeslayer and Saphira Bjartskular - Paolini, Christopher (Paolini, Christopher. Inheritance, 2008)
The further adventures of Eragon and his dragon Saphira as they continue to aid the Varden in the struggle against the evil king, Galbatorix.